Oligostilbenoids and phenolic compounds from the stem bark of Shorea materialis RIDL. (Dipterocarpaceae) - Muhammad Sulaiman Mohd Johari,; Nik Fatini Nik Azmin,; Wan Azmiza Syahira Wan Azhar,; Siti Zakirah Azahar,; Noorazlina Adnan,; Nurul Shahira Zakaria,; Fatimah Salim,; Norizan Ahmat,; Aisyah Salihah Kamarozaman, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Shorea genus is known for its abundance of sources of oligostilbenoids, which exhibit diverse biological functions. Nevertheless, despite its considerable potential, there remains a dearth of phytochemical investigations including Shorea materialis. Consequently, this study aims to isolate the chemical constituents from the stem bark of this species. The crude extract of S. materialis was obtained from the maceration technique and fractionation using vacuum liquid chromatography. The resulting fractions were further purified via column chromatography. The molecular structures of the isolated molecules were determined using various spectroscopic techniques. Two dimer stilbenoids, ampelopsins A (1) and D (2), three trimers, namely α-viniferin (3), hopeanolin (4) and davidiol A (5), one tetramer, vaticanol B (6), together with two phenolic compounds, p-hydroxybenzaldehyde and (7) 2,3,5-trihydroxy benzoic acid (8) were effectively isolated. The isolation of these compounds was the first report from this species.